(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
This paper examined the effect of the difference between the temperature of the two end of the body exposed to transient conduction heat transfer on the inception of thermal sensitivity and at different distances from the hot end of the sample. The study was based on the selection of a sample with a length of 15 cm and a fixed height of 1 cm. Four materials with different thermal properties were selected. One end of the model was exposed to three different temperatures (75, 125, and 175) oC. The other end of the sample was placed under a convection heat transfer at 25 oC. To adopt an inception indicator of thermal sensitivity of the sample when exposed to transient heat transfer, (26) oC was used because it is the nearest temperature to the initial condition of the sample. Four points were selected on different distance from hot end along the sample. The hot end temperature was also adopted as an indicator to measure the effect of the temperature difference for two body ends as the other end is subject to constant transient heat transfer. Determine the effect of the temperature difference between two body ends exposed to transient heat transfer on the inception of thermal sensitivity is study target. The results of this study showed the reverse effect of the temperature difference between two body ends exposed to transient heat transfer on the inception of thermal sensitivity, this effect increases by increasing the distance from hot sample end and depressing of thermal diffusivity. The results also showed that the values of the Thermal sensitivity inception ranged between (0.43-17845) seconds according to the distance from the hot end, its temperature, and the thermal diffusivity of sample materials for each case.